Effects of the local purple sticky rice bran extract on antioxidant activity and calcium oxalate crystal formation and aggregation in vitro - Nuurai, Parinyaporn; Khawsuk, Witoon; Semangeon, Tistaya (Journal of Health Science and Alternative Medicine, 2022)
Introduction: Kidney stone disease is a common urological disorder affecting human health. Inhibition of calcium oxalate (CaOx) formation and aggregation can prevent the recurrence of kidney stones. Pigmented rice has been studied for various functions including antioxidant activity, anti-inflammation, antidiabetic, anticancer, and antiaging. However, the function of purple rice bran on the antioxidant activity related to the kidney stone disease is limited. Objective: To investigate the effect of the purple sticky rice bran (PSB) extract obtained from the local strain at Songkhla province on its antioxidant activity and subsequent in vitro inhibition of CaOx crystal formation and aggregation. Methodology: The PSB ethanol extract was prepared at different concentrations (0.025–1.4 mg/mL). The levels of anthocyanin and total phenolic compounds were analyzed using pH differential and the Folin–Ciocalteu reagent methods. The antioxidant activity of PSB extract was determined using the DPPH assay and FRAP. The formed CaOx crystals were incubated with the PSB extract at different concentrations (20 - 400 µg/mL). The number of CaOx crystals and their aggregation forms were determined and compared with the control. Results: The levels of anthocyanin and total phenolic compounds in PSB extract were 18.67 ± 1.50 µg/g and 34.70 ± 1.64 mg gallic acid equivalent/g of rice bran, respectively. The DPPH free radical scavenging antioxidant activity and ferric-reducing antioxidant power increased after the concentration of the PSB extract was increased. The IC50 of ascorbic acid and PSB extract were 0.016 and 0.07 mg/ml, respectively. The PSB extract significantly decreased the formation and the number of CaOx crystals. Moreover, the high concentration of PSB extract augmented the calcium oxalate dihydrate (COD) crystal formation rather than the monohydrate crystal formation. Furthermore, it inhibited the CaOx crystal aggregation in a dose-dependent manner. Conclusion: PSB extract contained substances with high antioxidative activity and could suppress the CaOx crystal formation and aggregation. This study can be helpful to the researchers in the development of strategies for the prevention of kidney stones.